Role of Cerebro-Placental Ratio in prediction of adverse perinatal outcome in hypertensive disorder of pregnancy (Nepal Medical College Journal, 2022)
Hypertensive disorder of pregnancy is a multisystem disorder associated with an increased risk of perinatal mortality worldwide. Doppler velocimetry of uterine, umbilical, and fetal vessels is an established method of antenatal monitoring identifying fetus at risk. The cerebroplacental ratio (CPR) is emerging as an important predictor of the adverse perinatal outcome as it considers both umbilical and middle cerebral artery doppler. The aim of this study is to find the role of CPR in the prediction of adverse perinatal outcome in the hypertensive disorder of pregnancy. A prospective descriptive study was done on women admitted to a tertiary care hospital in Kathmandu from July 2020 to June 2021 after taking ethical clearance from Institutional Review Committee. A total of 136 hypertensive pregnant women beyond 34 weeks of gestation underwent Doppler ultrasound, and CPR ratio